2015
DOI: 10.1111/pde.12592
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cyclosporine Weekend Therapy: A New Maintenance Therapeutic Option in Patients with Severe Atopic Dermatitis

Abstract: Cyclosporine A (CyA) is a systemic therapy used to control severe atopic dermatitis (AD) in children, but its use may be associated with serious side effects. Intermittent short-course therapy has been used to minimize these risks without the loss of clinical benefits. We conducted a 20-week study using intermittent short-course CyA therapy in five patients with severe AD and a Scoring Atopic Dermatitis (SCORAD) score >40. The result was a reduction in the cumulative dose of CyA and serum CyA level, which allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Significant creatinine rise in the pediatric trials varied from 0% to 9.3%. Berth‐Jones, Sarıcaoğlu, and Garrido Colmenero all reported no incidence of clinically significant creatinine rise, while Harper, Yee, and Zaki reported 9.3%, 7%, and 5%, respectively. El‐Khalawany reported that 15% of participants developed renal dysfunction; Bunikowski reported 10% had a rise in creatinine (not otherwise defined); and in Hernandez‐Martin's cohort, 3% had a transient rise in urea nitrogen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Significant creatinine rise in the pediatric trials varied from 0% to 9.3%. Berth‐Jones, Sarıcaoğlu, and Garrido Colmenero all reported no incidence of clinically significant creatinine rise, while Harper, Yee, and Zaki reported 9.3%, 7%, and 5%, respectively. El‐Khalawany reported that 15% of participants developed renal dysfunction; Bunikowski reported 10% had a rise in creatinine (not otherwise defined); and in Hernandez‐Martin's cohort, 3% had a transient rise in urea nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Hernandez‐Martin used a mean initial dose of 4.3 mg/kg. Sarıcaoğlu and Bunikowski used 2.5‐5 mg/kg daily and 2.5 mg/kg, respectively, initially, also titrated to clinical response, and Garrido Colmenero used weekend dosing—5 mg/kg given Saturday and Sunday only. El‐Khalawany administered 2.5 mg/kg daily Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ciclosporin over the weekend,36 akin to topical proactive treatment, as a maintenance therapy to reduce the risk of relapse was also explored.…”
Section: Ciclosporinmentioning
confidence: 99%